Pengaruh Lebar Cetakan Komposit Karbon Aktif-Tembaga (ii) Oksida terhadap Karakteristik Termoelektrik - Sari, Putri Manda; Putra, Ananda (MASALIQ, 2023)
This research aims to determine the effect of the width of the C-CuO composite mold on the characteristics of thermoelectric materials. The composite is made from activated carbon mixed with CuO in a ratio of 3 grams of activated carbon: 7 grams of CuO which is then molded with five variations in the width of the mold for the C-CuO composite, namely 1 cm, 1.3 cm, 1.6 cm, 2 cm and 2.5 cm. In testing the electrical conductivity and Seebeck effect on the C-CuO composite, the values were almost the same, in other words the electric current produced was not influenced by the mold width of the C-CuO composite. Meanwhile, on the heat conductivity day value, the mold width has an influence as the applied temperature increases. Where the optimum heat conductivity value is produced in material with a width of 1 cm.